2012
DOI: 10.1073/pnas.1118458109
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor (PPAR)α and -γ regulate IFNγ and IL-17A production by human T cells in a sex-specific way

Abstract: Women develop certain autoimmune diseases more often than men. It has been hypothesized that this may relate to the development of more robust T-helper (Th)1 responses in women. To test whether women exhibit a Th1 bias, we isolated naïve cluster of differentiation (CD)4 + T cells from peripheral blood of healthy women and men and measured the proliferation and cytokine production by these cells in response to submaximal amounts of anti-CD3 and anti-CD28. We observed that CD4 + T cells from women produced highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
177
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(195 citation statements)
references
References 36 publications
5
177
2
2
Order By: Relevance
“…By contrast, in immune cells PPAR primarily inhibits inflammatory pathways by repressing c-jun and NF-κB [11,12]. PPAR also inhibits IFN responses of human  T cells [13]. Whether PPAR also regulates human  T cell functions remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…By contrast, in immune cells PPAR primarily inhibits inflammatory pathways by repressing c-jun and NF-κB [11,12]. PPAR also inhibits IFN responses of human  T cells [13]. Whether PPAR also regulates human  T cell functions remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…One intriguing feature of Th1 immune responses is that they are more robust in females than in males (5)(6)(7)(8). This sex difference is thought to underlie why women generate enhanced antiviral (9) and antitumor (10) immune responses, but also have a higher propensity to develop certain autoimmune diseases (8).…”
mentioning
confidence: 99%
“…This sex difference is thought to underlie why women generate enhanced antiviral (9) and antitumor (10) immune responses, but also have a higher propensity to develop certain autoimmune diseases (8). Past studies have suggested that sex differences in Th1 responses arise because of suppressive effects of androgens at key nodes in the Th1 differentiation pathway including IL-12 production (11) and signaling (12,13) and IFN-g production downstream of Ag stimulation (6,7). Until recently, the molecular players involved in this androgen-dependent regulation were not known.…”
mentioning
confidence: 99%
“…Female immune responses are tilted to Th1 with the dominance of IFN-γ, whereas male responses are pushed to Th17, dominated by IL-17 and IL-23. Dunn showed that this was true across species from mice to humans (97,98). Because PPAR-α is targeted by widely used drugs such as gemfibrozil, this dimorphism provides clues that can be translated to therapy with widely used approved drugs for other indications.…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%
“…Shannon Dunn tackled this problem while a postdoc and has continued her brilliant work in a faculty position at the University of Toronto. We published a series of reports in the Journal of Experimental Medicine and Nature Medicine (96)(97)(98) describing the role of peroxisome proliferator-activated receptor (PPAR)-α and PPAR-δ in regulating the sexual dimorphism. PPAR-α is overexpressed on male T cells.…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%